2013
DOI: 10.1016/j.chemphyslip.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential scanning calorimetric evaluation of human meibomian gland secretions and model lipid mixtures: Transition temperatures and cooperativity of melting

Abstract: Meibomian gland secretions (or meibum) are produced by holocrine meibomian glands and are secreted in melted form onto the ocular surface of humans and animals to form a protective tear film lipid layer (TFLL). Its protective effect strongly depends on the composition and, hence, thermotropic behavior of meibum. The goal of our study was to quantitatively evaluate the melting characteristics of human meibum and model lipid mixtures using differential scanning microcalorimetry. Standard calorimetric parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Squalene has a much lower melting point (−75°C) than the transition temperature of both sebum (Table 2) and meibum (28–35°C). 57,69,70 A ratio of SQ well above expected physiological levels was used to clearly delineate an effect should one occur. Squalene caused significant ( P < 0.05) changes in the phase transition parameters for a pool of human meibum (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Squalene has a much lower melting point (−75°C) than the transition temperature of both sebum (Table 2) and meibum (28–35°C). 57,69,70 A ratio of SQ well above expected physiological levels was used to clearly delineate an effect should one occur. Squalene caused significant ( P < 0.05) changes in the phase transition parameters for a pool of human meibum (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Monolayers of tear film-like wax esters can retard evaporation when used at temperatures 3 °C lower than their bulk melting temperature [258,260,261]. However, meibum has a much more complex composition, structure and thermotropic behavior compared to the model films, and the melting temperature of meibum (~30 °C) [262264] is lower than the ocular surface temperature (35 °C). Recently in vitro studies with the Interfacial Dewetting and Drainage Optical Platform (i-DDrOP) on silicone hydrogel (SiHy) contact lenses have shown that the mucoaqueous subphase beneath thinner parts of meibomian films thins and dewets faster compared to that seen below thicker “islands” in the meibomian layer [265].…”
Section: Biophysical Studies Of Tearsmentioning
confidence: 99%
“…Data on the thermotropic phase transitions (via spectroscopy, differential scanning calorimetry and X-ray diffraction studies) [262,264,301303] and interfacial and bulk rheology [29,301,302] of tear lipids in vitro and in vivo , suggest a thick viscoelastic duplex structure composed of a monomolecular layer of amphiphilic polar lipids at the mucoaqueous surface and a generally unstructured shear thinning lipophilic suspension at the lipid-air interface. The lipophilic suspension consists of lipid lamellar-crystallite particulates immersed in a continuous liquid phase with no long-range order.…”
Section: Biophysical Studies Of Tearsmentioning
confidence: 99%
See 2 more Smart Citations